Lung Cancer Treatment: From Tradition to Innovation - Mangiameli, Giuseppe; Cioffi, Ugo; Testori, Alberto (Frontiers in Oncology, 2022)
Lung cancer (LC) is the second most commonly diagnosed cancer and the primary cause of cancer death worldwide in 2020. LC treatment is associated with huge costs for patients and society, consequently there is an increasing interest on prevention, early detection with screening, and development of new treatments. His surgical management accounts for at least 90% of the activity of thoracic surgery departments. Surgery is the treatment of choice for the early-stage non-small cell lung cancer. In this article, we discuss the state of art of thoracic surgery for surgical management of LC. We start describing the milestones of LC treatment that are lobectomy and an adequate lymphadenectomy, then we focus on the traditional and innovative mini-invasive surgical approaches actually available: video-assisted thoracoscopic surgery (VATS) and robotic assisted thoracoscopic surgery (RATS). A brief overview about the innovation and future perspective in thoracic surgery will close this minireview.